MENINGKATKAN KEMAMPUAN HAFALAN JUZ ‘AMMA MELALUI METODE MURAJA’AH BERKELOMPOK DI UPTD SPF SDN SIANJO ANJO MERIAH - Siswanti; Misnawati (Madrasa : Jurnal Ilmu Pendidikan dan Teknologi, 2025)
This study aims to improve students' Juz 'Amma memorisation skills through the application of the group muraja'ah method at the UPTD SPF SDN Sianjo Anjo Meriah. This study uses a Classroom Action Research (CAR) design with two cycles, each consisting of planning, implementation, observation, and reflection stages. The research subjects were 25 fourth-grade students. The research instruments included observation sheets, memorisation tests, and reflection notes. The results showed a significant improvement in students' memorisation skills. In cycle I, 64% of students achieved the mastery criteria, while in cycle II, this increased to 88%. In addition, students showed more enthusiasm, activity, and motivation in repeating memorisation in groups. Thus, the group muraja'ah method is effective in improving Juz 'Amma memorisation skills while fostering togetherness and enthusiasm for learning among students.